2016
DOI: 10.1021/acs.joc.6b01217
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Photocatalytic Radical–Radical Cross-Coupling Reactions of Amines and Carbonyls: A Route to 1,2-Amino Alcohols

Abstract: An intermolecular radical-radical cross-coupling reaction of secondary and tertiary amines with aryl ketones and aldehydes has been developed using visible light photoredox catalysis. This reaction provides an efficient and straightforward approach to some useful 1,2-amino alcohols in moderate to good yields under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 64 publications
0
38
0
1
Order By: Relevance
“…Previous reports of visible‐light induced ketyl radical formation reactions are enhanced by the addition of acids, which were consistent with this reaction when a catalytic amount of oxalic acid was added (entry 4, 63 % yield). Furthermore, to suppress the possible formation of undesired diol, and coordinate α‐amino radical and ketyl radical cross‐coupling by Li + , we added a lithium salt (LiBF 4 , 1 equiv) to the reaction mixture and found that the yield improved to 72 % (entry 5, 70 % isolated yield). In the absence of DABCO and acid, a sharp decrease in efficiency was found (entry 6), which indicated that the lithium salt serves as a Lewis acid to induce a Lewis acid‐activated single electron transfer (SET) process to afford corresponding ketyl radical is impossible .…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports of visible‐light induced ketyl radical formation reactions are enhanced by the addition of acids, which were consistent with this reaction when a catalytic amount of oxalic acid was added (entry 4, 63 % yield). Furthermore, to suppress the possible formation of undesired diol, and coordinate α‐amino radical and ketyl radical cross‐coupling by Li + , we added a lithium salt (LiBF 4 , 1 equiv) to the reaction mixture and found that the yield improved to 72 % (entry 5, 70 % isolated yield). In the absence of DABCO and acid, a sharp decrease in efficiency was found (entry 6), which indicated that the lithium salt serves as a Lewis acid to induce a Lewis acid‐activated single electron transfer (SET) process to afford corresponding ketyl radical is impossible .…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, the researchers from the group of Xiao were able to generate the α-amino radical of 3,4-dihydroquinoxalin-2-one (among other amines) using fac-Ir(ppy) 3 as photocatalyst. [83] They reported just two examples in which this radical was coupled with benzophenone through its lithium-bonded ketyl radical (Scheme 64). These researchers were also capable of proposing a mechanistic pathway by which its developed reaction should proceed.…”
Section: Functionalization Of Dihydroquinoxalin-2onesmentioning
confidence: 99%
“…While in Wang's work, the authors proposed a proton-coupled electron transfer (PCET) pathway of the complex containing the aldehyde, DABCO, and a protonic acid (Scheme 21). Since 2016, Xiao's group [49] and Wang's group [50] have developed the photocatalytic benzylation of glycine derivatives with ketones and aldehydes, respectively, to produce useful 1,2-amino alcohols in moderate efficiency. Xiao and coworkers believed that the lithium salt LiBF 4 took the important role as a Lewis acid in the activation of the ketones to the corresponding ketyl radical (Scheme 20).…”
Section: C(sp 3 )-H Benzylationmentioning
confidence: 99%